Synthesis and characterisation of new copper(II) coordination polymers constructed from pyrazine–tetrazole ligands with the formation of a water cluster. Issue 7 (2nd August 2016) - Sheridan, Ursula; Gallagher, John F.; Fadda, Elisa; Bjerrum, Morten J.; McGinley, John
Abstract: Three novel bis-tetrazole ligands (1–3 ) containing carboxylate functional groups on the tetrazole rings and a rigid pyrazine linker unit, for the construction of coordination polymers when coordinated to copper(II) ions, were synthesised and structurally characterised. The use of pyrazine as a rigid linker between the two tetrazole units was expected to increase the dimensionality of the solid phase polymeric network of the resulting copper(II)-containing compounds. X-ray structures of the ligands revealed the effect of the substitution position on the tetrazole ring of the ester/carboxylate groups. Higher solid phase dimensionality was successfully achieved as shown by the layered two-dimensional (2-D) coordination structure being formed when the pyrazine bis-tetrazole systems were reacted with copper(II) chloride, although not in the expected manner. There was no interaction between the pyrazine nitrogen atoms and the metal ion. Computational studies showed that this was probably due to the geometry, required by the copper ion, to be involved in the close packing between the layers. The 2-D coordination polymer based on the asymmetric substituted pyrazine bis-tetrazole, [ Cu(4 )(H2 O)](H2 O)2, was further connected into a three-dimensional (3-D) coordination network through hydrogen bonding between H2 O molecules. These H2 O molecules were connected as a unique 1-D chain throughout the structure. Abstract : Three novel bis-tetrazole ligands (1 -3 ) containing carboxylate functional groups on the tetrazole rings and a rigid pyrazine linker unit, for the construction of coordination polymers when coordinated to copper(II) ions, were synthesised and structurally characterised.